Hegel : A Very Short Introduction - Singer, Peter, 1946- (Oxford, New York Oxford University Press, 2001)
Many people regard Hegel's work as obscure and extremely difficult, yet his importance and influence are universally acknowledged. Peter Singer eliminates any excuse for remaining ignorant of the outlines of Hegel's philosophy by providing a broad discussion of his ideas and an account of his major works.
Include Index and Illustration
Keywords: Hegel, Georg Wilhelm Friedrich, 1770-1831 -- Philosophy, German